More Adaptive Educational Supervision: A Study of Principle Variance - Sari, Lidya Puspita; Ramadhan, Alfa Rezky; Herawati, Endang Sri Budi; Muhammad, Amiruddin; Wijaya, Widia Murni (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2026)
This study aims to identify educational supervision principles that can be adopted by practitioners to address the specific needs and challenges of educational institutions and to enhance educational quality sustainably. The study employed a Systematic Literature Review (SLR) using the PRISMA approach. Eighteen articles met the inclusion criteria and were analyzed, while 306 were excluded. The review identified 15 key principles of educational supervision: collaborative, democratic, needs-based, adaptive, sustainable, participatory, scientific, continuous improvement-oriented, supportive, evaluative, humanistic, innovative, flexible, professional development-oriented, and accountable. Their application varies according to contextual challenges such as limited teacher competence, geographical constraints, inadequate facilities, and diverse socio-cultural backgrounds. In institutions with limited training access, needs-based and collaborative supervision effectively supports teacher development through mentoring and peer learning communities. In remote schools, adaptive and flexible supervision can be implemented through online platforms for observation and feedback. The findings indicate that effective supervision requires contextual sensitivity, flexibility, strategic use of digital technologies, and trust-based professional relationships. The study proposes three theoretical frameworks: (1) the context-sensitive supervisory innovation rule, emphasizing alignment between management practices and institutional readiness; (2) the digital relational supervision theory, integrating data-driven technologies with collaborative and humanistic relationships; and (3) the sustainable supervisory learning theory, conceptualizing supervision as a continuous cycle linking evaluation, reflection, and professional development to promote long-term improvement in teaching and learning across diverse contexts.